BOBOBEK AND JORABEK - PATRIOTS FIGHTING AGAINST THE COLONIAL POLICY OF THE RUSSIAN EMPIRE - Abdimitalov Davronbek Abdug‘ani o‘g‘li (Journal Park Publishing, 2022)
This article provides a scientific analysis of Jo‘rabek, the patriotic ruler of Shakhrisabz, who fought against the colonial policy of the Russian Empire.
Keywords: Amir; toqsaba; beklik